Visualizing recombination intermediates with single-stranded DNA curtains - Qi, Zhi (Methods, 2016)
Homologous recombination (HR) is a critical cellular process for repairing double-stranded DNA breaks (DSBs) – a toxic type of DNA lesion that can result in chromosomal rearrangements and cancer. During the early stages of HR, members from the Rad51/RecA family of recombinases assemble into long filaments on the single-stranded DNA overhangs that are present at processed DSBs. These nucleoprotein filaments are referred to as presynaptic complexes, and these presynaptic complexes must align and pair homologous DNA sequences during HR. Traditional ensemble methods cannot easily access the transient and often heterogeneous intermediates that are typical of DNA recombination reactions, and as a consequence, there remain many open questions with respect to the molecular details of this pathway. Novel single-molecule approaches that are capable of directly visualizing reaction intermediates in solution and in real time offer the potential for new insights into the mechanism of homologous DNA recombination. Here we highlight recently developed single stranded DNA curtain methods for studying the properties of individual Rad51 presynaptic complexes and other related recombination intermediates at the single-molecule level.